2019
DOI: 10.33314/jnhrc.v0i0.1628
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Care Practices at Home among Mothers of Neonates Admitted with Sepsis

Abstract: Background: Child rearing practices and family environment determine the health of newborn. Harmful newborn care practices are the risk factors for late onset neonatal sepsis. The objective was to identify newborn practices related to breast feeding, cord care, hygiene of newborn and thermal care practice at home of admitted neonates with diagnosis Late Onset Neonatal Sepsis in pediatric unit of B.P. Koirala Institute of Health Sciences tertiary center in eastern Nepal.Methods: Descriptive cross sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
3
1
0
Order By: Relevance
“…This result was in line with a study by Gul et al [ 30 ], which found that a woman’s wealth status is directly related to her use of LNB. This was also in line with Chhetri et al [ 31 ], who discovered that wealth status has a role in LNB practice. Similarly, Adegun et al [ 32 ] found that wealth status was positively related to LNB in an Ibadan study.…”
Section: Discussionsupporting
confidence: 89%
“…This result was in line with a study by Gul et al [ 30 ], which found that a woman’s wealth status is directly related to her use of LNB. This was also in line with Chhetri et al [ 31 ], who discovered that wealth status has a role in LNB practice. Similarly, Adegun et al [ 32 ] found that wealth status was positively related to LNB in an Ibadan study.…”
Section: Discussionsupporting
confidence: 89%
“…This result was in line with a study by Gul et al [30], which found that a woman's wealth status is directly related to her use of LNB. This was also in line with Chhetri et al [31], who discovered that wealth status has a role in LNB practice. Similarly, Adegun et al [32] found that wealth status was positively related with LNB in an Ibadan study.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, 73.6% practiced hand washing before touching the baby, 20.8 use oil to care umbilical cord, 1.6% apply Kajal in the eyes which is similar to the study conducted by Chhetri BT, et al (2014) found out that 62.5% practiced hand washing before touching the baby, 72.5% use mustard oil to care umbilical cord, 52.5% apply Kajal in the eyes [6] .…”
Section: Discussionsupporting
confidence: 88%